Motor Service's Automotive Encyclopedia / Fundamental Principles, Operation, Construction, Service, Repairs - Johnson Larry; Toboldt William K (Goodheart-Willcox, Co. Inc, 1970)
Automotive Tools, Fastening Devices, Linear Measuring Instruments, Engine Fundamentals, Engine Construction, Engine Piston and Rings, Engine Crafkshafts and Camshafts, Engine Bearings and Valves, Engine Performance, Engine Lubrication, Engine Cooling Systems, Other Engines, Engine Reconditioning, Piston Ring and Pin Fitting, Crankshaft Wear, Valve Service, Engine Trouble-Shooting, Engine Tune-Up, Auto Shop Safety, Automotive Fuels, Principles of Carburetion, Manual and Automatic Chokes, Engine Manifolds, Air Cleaners, Carburetor Adjustment and Service, Fuel Supply Systems, Fuel Injection, Exhaust Systems, Exhaust Emission Control, Fundamentals of Electricity and Magnetism, Generators and Alternators, Generators and Alternator and Testing and Servicing, Generator and Alternator and Regulators and Relays, Starting Motor Fundamentals, Engine Ingnition, Meters, Clutches, Drive Line Service, Tires and Tire Service, Job Opportunities, Index.